PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERMAIN PERAN TERHADAP KETERAMPILAN MENYAMPAIKAN TEKS NEGOISASI SISWA KELAS X SMA N 1 RANAH PESISIR - Mai Mela Sari (STKIP PGRI Sumatera Barat, 2021)
This research is motivated by the low interest of students in speaking. This study aims to describe the skills of conveying the negotiation text of students before and after using the role playing learning model and the influence of the role playing model on the delivery of negotiation text skills in class X SMA N 1 Ranah Pesisir. This type of research is quantitative with experimental methods.The sample in this study were 24 students of class X IPA 1. The data in this study were the skills scores of Submitting Negotiation Texts before and after the role playing model of class X students of SMA N 1 Ranah Pesisir. The results of this study can be concluded as follows. First, the skill of conveying the negotiation text before using the role playing learning model obtained an average score of 65.51 with sufficient qualifications (C). Second, the skill of delivering negotiation texts after using the Role Play learning model has an average score of 76.15 with good qualifications (C). Third, based on the t-test, there is an effect of the Role Play learning model on the skills of conveying negotiation text for class X SMA N 1 Ranah Pesisir because tcount = 6.67 and t table = 1.71. accepted and H0 rejected.